A survey on key technologies of privacy leakage detection for Android platform. (January 2020) - Yu, Fu; Xuming, Lv; Xiao, Gao; Lin, Liu; Jingzhao, Luan
Abstract: With the rapid advancement of the mobile internet, smartphones have been the essential tools for communication and entertainment. In recent years, Android, developing quickly, has been the largest mobile operating system in the world. However, due to mass private data generated by Android intelligent devices, privacy disclosure is a serious problem in security for the Android platform. Based on the relevant background, this thesis indicates the problems of privacy protection that the Android platform faces, summarizes the detecting techniques for privacy disclosure on the Android platform at the present stage, and introduces the research status and progress with the aim of offering a reference for relevant practitioners and researchers.